Health economics in development - Musgrove, Philip; World Bank. (Washington, D.C. : World Bank, 2004)
Explains basic concepts, for the benefit of non-economists working in public health and further develops some of those concepts to show how they can be applied to real situations.
Articles previously published in various sources between 1980 and 2001.
Includes bibliographical references and index.
oif 07/08/15
Loan
Keywords: Economics, Medical -- Collected Works; Developing Countries -- Collected Works